Cover Jurnal Fitopatologi Vol. 18 No. 6, November 2022 - Editors Jurnal Fitopatologi Indonesia (Jurnal Fitopatologi Indonesia, 2023)
This editorial contains the front cover, editorial page, and back cover of the Jurnal Fitopatologi Indonesia Vol. 18 No. 6, November 2022